Skin diseases of the nipple and areola complex: A case series study from China - Wu, Chao; Jia, Qian-Nan; Fang, Kai; Zeng, Yue-Ping (Frontiers in Medicine, 2023)
Background: Skin diseases of the nipple and areola complex are numerous and difficult to diagnose, which is a great challenge for clinicians. A better understanding of the clinical features of nipple and areola complex skin diseases is of great value for the correct diagnosis. Methods: To investigate the clinical characteristics of skin diseases of the nipple and areola complex, we retrospectively analyzed the demographic data, disease constitution, rash characteristics, inconsistency between the clinical and pathological diagnosis from 260 patients with nipple and areola complex lesions that were confirmed by histopathology at Peking Union Medical College Hospital, China from 2012 to 2022. Results: The patients’ average age was 43.6 (8 to 82) years, and the ratio of females to males was 13.4:1. Out of the 260 patients biopsied, the most common diseases were eczema, Paget’s disease, adenoma of the nipple, seborrheic keratosis, cutaneous metastasis of breast cancer, wart, soft fibroma, and hyperkeratosis of the nipple and areola. There were 77 (29.6%) patients with inconsistency between the clinical impressions and pathological diagnoses. Adenoma of the nipple was the most clinically misdiagnosed condition, most commonly presumed to be Paget’s disease or eczema. Conclusions: Eczema and Paget’s disease are the most common biopsied nipple and areola complex skin diseases. Late onset, unilateral involvement, and predilection for the nipple are several characteristics of Paget’s disease, which are different from eczema. Nipple and areola complex skin diseases are easily misdiagnosed clinically, especially adenoma of the nipple.